ENGLISH LANGUAGE DIFFICULTIES AND STUDY HABITS OF INDONESIAN UNIVERSITY EXCHANGE STUDENTS STUDYING IN AN INTERNATIONAL PROGRAM AT RAJAMANGALA UNIVERSITY OF TECHNOLOGY KRUNGTHEP THAILAND: ENGLISH LANGUAGE DIFFICULTIES AND STUDY HABITS OF INDONESIAN UNIVERSITY EXCHANGE STUDENTS STUDYING IN AN INTERNATIONAL PROGRAM AT RAJAMANGALA UNIVERSITY OF TECHNOLOGY KRUNGTHEP THAILAND - White, Alan Robert; Darodjat, Tubagus Achmad; Prasetyo, Dedy Ardian (Yayasan Pusat Cendekiawan Intelektual Nusantara, 2024)
This study examines the experiences of 32 Indonesian students enrolled in an international business program at a Thai university, focusing on their difficulties, motivation, and attitudes towards learning English. Data were collected through a 5-point Likert scale questionnaire and interviews. The research investigates factors such as language difficulties, anxiety, study habits, and the motivation to improve language skills. The results indicate that students face moderate difficulties in mastering English, but their motivation to learn the language is high. Anxiety related to speaking English is present but not overwhelming. Students’ study habits are slightly above neutral, suggesting room for improvement in learning strategies. Despite facing difficulties, students express a strong interest in improving their English proficiency. They enjoy listening to music and watching films in English. The study points to the need for tailored support to address language anxiety and study habits to help students succeed in language learning and academic work. The findings stress the importance of creating a positive and engaging learning environment that promotes linguistic and personal development.